JOB INVOLVEMENT AND SERVANT LEADERSHIP INFLUENCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN EMPLOYEES - Tentama, Fatwa; Salsabila, Andi Lutfiyah Nada (Program Studi S1 Psikologi, 2023)
This study aims to test job involvement and servant leadership influence on Organizational Citizenship Behavior (OCB) in employees. Participant in this research was 70 permanent employees in an